Asesmen dan Penyusunan Program Pendidikan Individual Bagi Anak Berkesulitan Belajar Spesifik - Miftahul Aula Saadah (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2018)
Children with learning disability are children who have disability in academic tasks caused by minimal brain dysfunction or in basic psychology, so that the learning achievement is not in accordance with the actual potential and to develop their potential optimally require special education. Learning disabilities that are internal [learning disability] and learning disabilities that are external [learning problem] show almost the same symptoms that is the disability in learning mathematics/dyscalculis, dyslexia and dysgraphia and the existence of difficulties in behavior. Therefore, to recognize the difficulty of learning can be done by looking for links between academic skills [dyslexia, dysgraphia, and dyscalculis] with pre-academic skills [linguistic awareness and basic cognitive process skills] through the identification process. After the identification then proceed with the assessment process to find out the needs of children who will be used in preparing individualized education program.